A Nonlinear Forecasting Model of GDP Growth - DeJong, David N.; Liesenfeld, Roman; Richard, Jean-François (The Review of Economics and Statistics, 2005)
We develop a model of GDP growth under which regime changes are triggered stochastically by an observable tension index, constructed as the geometric sum of deviations of actual GDP growth from a corresponding sustainable rate. Within expansionary regimes, the tension index tends to increase, which heightens the probability of a regime change. Given a regime change, the process becomes reversed, and the tension index begins to decline along a newly established path. Linking the behavior of the tension index to GDP growth enables us to capture floor and ceiling effects.